621.314.212 RELEVANCE OF RESEARCH ON FAILURE TO POWER TRANSFORMERS, REVIEW - Abdullaev, Abduvokhid; Nasretdinova, Feruza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This review article examines the current status of the topic by analyzing the scientific papers published in the last fifty years in the IEEE Xplore database related to power transformer faults. In this article, organizations, regions, and publishing houses dealing with power transformer damage are analyzed, and the share of journals and conferences in general publications is given. At the same time, foundations sponsoring scientific research and foreign scientists who wrote dissertations in this field are cited. The IEEE Xplore and Google Scholar databases were used to construct the graphs. Systematic analysis was used to construct charts of published scientific works. Statistical analysis was used to construct a list of organizations that published scientific works related to the topic, to determine the share of journals and conferences in the publications. The results of the analysis showed that the number of publications on the fault of power transformers is continuously increasing from year to year, which indicates that the field is becoming more relevant. Especially in Beijing, many scientific works have been published on the topic. Foundations can be found on all continents. In the future, they can use this article as analyzed data in researching power transformer damage.